Academic knowledge of Medicine and Nursing students on organ donation for transplants - Oliveira, Genilde Gomes de; Nogueira, Emília Cervino; Lima, Izabel Cristina de Oliveira (Brazilian Journal of Transplantation, 2010)
Purposes: To identify knowledge of students from the Academy of Medicine and Nursing of the Federal University of Sergipe related to the organ and tissue donation for transplants and the legislation and criteria to confirming the brain death (BD) diagnosis, to understand if religion interferes in the perception and to identify whether those students talk about organ donation t their family or friends. Methods: Quantitative, descriptive and cross study with 85 students from the UFS, 22 of Nursing and 63 of Medicine, who answered a semi structured questionnaire with 20 questions. Results: Group between 16 and 34 years old, 55.3% female, predominantly Catholic (71.7%). The majority (75.3%) reported their religion is not clear about organ donation and transplantation. 80% was aware of the transplantation laws, 87% believe that tBD is equal to cardio-respiratory arrest, 52.9% claimed to know protocol for the diagnosis of BD, while the same percentage responded that there is no difference in the adult and children diagnosis, 70.6% know the need for additional examination and 65.9% know it is required at least two doctors to testify the BD, but 45.9% believed that the minimum clinical reassessment of ME in adult is two hours. As to the knowledge on organ donation and transplantation after joining the Academia, 5.9% answered remain the same, 75.3% claimed to be higher and 18.8% believe it is lower. Although 40% said the ID Card is enough to authorize the donation, 76.5% said later that the only attitude required is to inform family. Conclusion: Nursing and medical students at the Federal University of Sergipe have little knowledge on organ and tissue donation for transplantation; the majority ignores the pertinent legislation, which may interfere in the involvement of students as professionals in the organ and tissue donation process for transplantation.